Analisis Tindak Pidana dan Tuntutan Korban terhadap Tersangka Afiliator Platform Binary Option Nomor 117/PID.SUS/2022/PT BTN - Taufik Tri Alpiansyah; Marjan Miharja; Lilis Purba (HUMANIORUM, 2023)
Binary options are online trading platforms offering funds in the form of money (forex), gold, silver and stocks. The problem that occurs in binary option transactions is not investment but is considered as online gambling, because it only predicts that assets have increased or decreased. The perpetrators attempted to carry out elements of money laundering from illegal investments in order to hide assets obtained from legal sources. Illegal investment is the main source of primary crime from money laundering. This study aims (1) to find out how the criminal act of a suspected binary option platform affiliator is. (2) What is the victim's claim regarding the suspected binary option platform affiliate, and (3) How is the prison sentence against the suspected binary option platform affiliate. The research method is normative juridical. The results of the study show that the criminal acts of suspected affiliators of the binary options platform are illegal investments and money laundering. The defendant Indra Kesuma was found to have violated the crime of money laundering and violating electronic transaction data violating the Prevention and Eradication of Money Laundering Crimes article 3 of Law Number 8 of 2010 and Article 45A paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. Indra Kesuma was sentenced to 10 years in prison, a penalty of 5 billion rupiah but can be replaced by 10 months in prison if not paid. The results of the confiscation of assets in the binary option case are returned to the victim. The prison sentence for the alleged affiliator Indra Kesuma is in accordance with applicable law.